Illicit tobacco trade is 'booming': UK newspaper coverage of data funded by transnational tobacco companies. Issue Volume 29:Issue e1(2020) (16th April 2020) - Evans-Reeves, Karen; Hatchard, Jenny; Rowell, Andy; Gilmore, Anna B
Abstract : Background: Transnational tobacco companies (TTCs) have heavily publicised their argument that standardised tobacco packaging will increase the illicit tobacco trade. Leaked Philip Morris International (PMI) documents suggest that the company may have intended to use third parties to promulgate this argument in the UK. Methods: We examined articles in UK newspapers (1 April 2013 to 31 March 2015) from LexisNexis for presence and nature of tobacco industry data. We also examined documents released by Freedom of Information requests made to Scottish Councils for evidence of how PMI operationalised its third-party strategy. Findings: Two-thirds of newspaper articles (63%, 99/157) mentioned a PMI consultant; 36% of which did not disclose this industry funding. Most articles mentioned counterfeit tobacco, illicit whites or both (72%, 113/157), while few (4%, 7/157) specifically mentioned tobacco industry illicit tobacco and none explained that the latter can include tobacco-company involvement. Freedom of Information documents revealed that the PMI consultant sought to build relationships with Trading Standards officers, conducted undercover test purchases (UTPs) in illicit tobacco 'hotspots' and may have promoted unrepresentative findings in the media. While the data set featured PMI data predominantly, other TTCs also engaged in third-party techniques to promulgate messages on illicit tobacco. Interpretation: PMI engaged a third party, seemingly with the aim of securing media coverage on illicit tobacco positing that standardised packaging would worsen the problem. The predominant focus of articles which featured industry-funded data and information was on counterfeit tobacco despite official data showing tobacco-industry illicit tobacco as the most prevalent. Other jurisdictions considering the policy should anticipate that third parties will promote the illicit-trade argument.